2014
DOI: 10.1007/s10985-014-9308-6
|View full text |Cite
|
Sign up to set email alerts
|

A consistent NPMLE of the joint distribution function with competing risks data under the dependent masking and right-censoring model

Abstract: Dinse (Biometrics, 38:417-431, 1982) provides a special type of right-censored and masked competing risks data and proposes a non-parametric maximum likelihood estimator (NPMLE) and a pseudo MLE of the joint distribution function [Formula: see text] with such data. However, their asymptotic properties have not been studied so far. Under the extention of either the conditional masking probability (CMP) model or the random partition masking (RPM) model (Yu and Li, J Nonparametr Stat 24:753-764, 2012), we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Thus, for the sake of model simplification, an independence assumption has traditionally been invoked between the various competing risks. Some recent research has focussed on developing dependent competing risks models (see Escarela & Carriere, 2003; Craiu & Reiser, 2006; Wang et al , 2012; Li & Yu, 2014). The complication of mutually dependent failure modes will not be considered in the ensuing theory.…”
Section: Definitions Notation and Terminologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for the sake of model simplification, an independence assumption has traditionally been invoked between the various competing risks. Some recent research has focussed on developing dependent competing risks models (see Escarela & Carriere, 2003; Craiu & Reiser, 2006; Wang et al , 2012; Li & Yu, 2014). The complication of mutually dependent failure modes will not be considered in the ensuing theory.…”
Section: Definitions Notation and Terminologymentioning
confidence: 99%
“…Wang et al (2012) proposed a new model for the NPMLE of intervalcensored and masked competing risks data, the random partition masking model, which does not rely on the assumption that masked failure causes are independent of failure time. Yu & Li (2012, 2014 examined the NPMLE proposed by Dinse (1982); they concluded that the NPMLE was inconsistent and not unique and they introduced a consistent NPMLE of the joint distribution function with right-censored and masked competing risks data under another new model (the dependent masking and right-censoring model).…”
Section: Introductionmentioning
confidence: 99%